Bilateral rotation flaps for the closure of a wound at the tail base of a cat - SELTZA (T. ΣΕΛΤΣΑ), J.; RABIDI (Σ. ΡΑΜΠΙΔΗ), S.; ELEKIDOU (Ε. ΕΛΕΚΙΔΟΥ), E.; DIDANGELOU (Χ. ΔΙΔΑΓΓΕΛΟΥ), C.; PAPAZOGLOU (Λ.Γ. ΠΑΠΑΖΟΓΛΟΥ), L. G. (Journal of the Hellenic Veterinary Medical Society, 2018)
A 2, 5 - year-old DSH female spayed cat was presented with a history of a tail base wound resulted from an abscess inflicted in a cat fight. The wound was managed initially as an open wound for 3 days and was covered with a bilateral rotation flap. One year after surgery the cat was reported to be in good health and the wound healed uneventfully.